Prenuptial Agreement as A Protection of Wife's Rights: Maqāṣid al-Syarī 'ah'ah's Analysis of The MUI Fatwa and The Constitutional Court's Decision - Sulaiman, Heri; Lubis, Rahmad; Muhammad, Muhammad; Dewi, Sri; Sriani, Arlina (al Hairy | Journal of Islamic Law, 2025)
This article examines the legal position of prenuptial agreements as an instrument for the protection of wife's rights in Islamic family law in Indonesia. Since the Constitutional Court Decision No. 69/PUU-XIII/2015, the urgency of the prenuptial agreement has increased because it is declared valid both before and after marriage. However, its role has not been fully understood as a protection mechanism for wives, especially in family economic justice. This study aims to analyze the legal position of prenuptial agreements in the perspective of the MUI Fatwa and the Constitutional Court Decision and evaluate its relevance through maqāṣid al-syarī'ah. The research method uses a normative qualitative approach through conceptual and juridical analysis. The results of the study show that the two legal instruments affirm the protection of wives on different grounds of argument: the MUI fatwa emphasizes sharia benefits and moral protection, while the Constitutional Court Decision affirms constitutional equality and distributive justice. Through the analysis of maqāṣid, the pre-marriage agreement has a preventive function that ensures the protection of property (ḥifẓ al-māl), the dignity of women (ḥifẓ al-'irḍ), and fair economic participation. Thus, the prenuptial agreement needs to be interpreted as a maqāṣid-based legal tool, not just an administrative agreement, but a substantive justice mechanism in contemporary Islamic family law,